Size dependent inherent antibacterial activity of polycation coated poly (lactide-co-glycolide) nanoparticles - Alhamvi, Shifa; Akgul, Busra; Akmayan, Ilkgul; Abamor, Emrah Sefik; Ozbek, Tulin; Topuzogullari, Murat (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
Bacterial infections, which are among the global causes of death, are becoming more difficult to treat due to antibiotic resistance. Therefore, new antibacterial materials are needed to selectively target bacteria and reduce the effect of antibiotic resistance. Polycations have emerged as a promising solution due to their inherent antibacterial properties, through directly interacting with the cell wall leading to bacterial disruption. In this study, poly(lactide-co-glycolide) (PLGA) nanoparticles (NPs) were coated with cationic copolymers of 4-vinylpyridine to produce inherently antibacterial polymeric NPs. Cationic NPs (CNPs) were prepared by coating the surface of PLGA NPs with varying concentrations of the polycation to evaluate the relationship between their size and antibacterial activity. Coating PLGA NPs with polycations resulted in highly positively charged CNPs with hydrodynamic diameters between 137 and 442 nm, low polydispersity indices (<0.25) and antibacterial activity against both S. aureus and E. coli. The findings revealed a size-dependent antibacterial effect, in which a total of 2290 CNPs of 137 nm hydrodynamic diameter were required to eradicate E. coli, while only 7 CNPs, with hydrodynamic diameter of 354 nm, effectively killed E. coli. At concentrations above their minimum inhibitory concentrations, CNPs are biocompatible, making them suitable for antibacterial biomedical applications.
Keywords: Antibacterial; Nanoparticles; PLGA; Polycations; Quaternization; ANTIMICROBIAL ACTIVITY; CATIONIC POLYMERS; DESIGN; Polymer Science